Feasibility of introducing Takaful (Islamic insurance) in India from the perspective of Islamic finance experts - Salman, Syed Ahmed; Hassan, Rusni; Yusoff, Adnan (R.K. Sharma, Institute of Medico-Legal Publications, 2018)
Objective: India as the second largest Muslim populated country has no practice with Takaful. This triggers the researchers to identify why Takaful has not been introduced in India. The main objective of this study is to scrutinize the perception and acceptability of Islamic finance experts to introducing Takaful in India. Analysis: The total 18 interviews have been conducted and all of them are male. Out of 18 interviewees, 12 are conducted through face to face interviews, and the remaining interview sessions were done either by phone calls or emails. Method: A combination of convenient sampling and purposive sampling method is used for selecting the Islamic finance experts as the respondents. Interview technique is the solely method used to collect the findings for this research. Findings: Four questions were asked to know the opinions of Islamic finance experts on the viability of Takaful in India. They are related to (Q1) possibility of introducing Takaful soon, (Q2) benefits of offering Takaful, (Q3) challenges to offer Takaful and (Q4) essential steps to be taken to start offering Takaful. Result: Regarding viability of Takaful, most of them share the positive view on this matter. In terms of operation, hybrid Wakalah-Mudarabah is the best suitable model for both general and family Takaful products.